Jewish women - Galor, Katharina, author.
1 online resource.
Keywords: "Jewish Women: Between Conformity and Agency examines the concepts of gender and sexuality through the primary lens of visual and material culture from antiquity through to the present day. The backbone of this transhistorical and transcontextual study is the question of Jewish women's agency in four different geographical, chronological, and methodological contexts, beginning with women's dress codes in Roman-Byzantine Syro-Palestine, continuing with rituals of purity in medieval Ashkenaz, worship in papal Avignon and the Comtat Venaissin, and ending with marriage and divorce in Israeli film. Each of these explorations is interested in creating a dialogue between the patriarchal legacy of the traditional texts and the chronologically corresponding visual and material culture. The author challenges traditional approaches to the study of Jewish culture by employing tools from art history, archaeology, and film and media studies. It is argued that, in each of these different contexts, there is ample evidence that women-despite persistent overall structural discrimination-have found ways to challenge male constructs of gender norms. Ultimately, these examples from past and present times highlight women's eminence in shaping Jewish history and culture. Bringing a new interdisciplinary lens to the study of the history of gender and sexuality, the book will be of interest to students and researchers of Jewish history and culture, art history, archaeology, and film studies"--